HUBUNGAN VISKOSITAS SALIVA DENGAN KEJADIAN KARIES GIGI PADA IBU HAMIL - Nuril Atqiya; Raden Harry Dharmawan Setyawardhana; Ika Kusuma Wardani (Universitas Lambung Mangkurat, 2021)
ABSTRACTBackground: Women are more susceptible to dental caries, especially in pregnant women. The prevalence of dental caries during pregnancy in developed countries is found to be 41%-52%, while in developing countries it is 60%-87%. Pregnant women have higher risk of dental caries compared to women who are not pregnant. The risk of dental caries can be assessed through changing saliva on pregnant women. Saliva viscosity can assess the risk of dental caries because if saliva viscosity increases it will result in ineffective cleaning of the oral cavity. Objective: To analyze the relationship of saliva viscosity with the incidence of dental caries in pregnant women. Method: This research used literature review method with narrative review procedure. Literature searches are done using Google Scholar and PubMed. Result: There were 30 journals that fulfilled this study by 2013-2020, Indonesian and English journals, available in full-text form, journals with discussion of saliva viscosity in pregnant women and dental caries in pregnant women. Conclusion: There was a relationship between saliva viscosity and dental caries in pregnant women. Keywords: Dental caries, pregnant women, salivary viscosity ABSTRAKLatar Belakang: Perempuan lebih rentan terhadap karies gigi, khususnya pada ibu hamil. Angka prevalensi karies gigi pada masa kehamilan di negara maju ditemukan sebesar 41%-52%, sedangkan di negara berkembang sebesar 60%-87%. Ibu hamil memiliki risiko karies gigi yang lebih tinggi dibandingkan dengan wanita yang tidak hamil. Risiko karies gigi dapat dinilai melalui perubahan saliva ibu hamil. Viskositas saliva dapat menilai risiko dari karies gigi karena jika viskositas saliva meningkat akan mengakibatkan pembersihan rongga mulut menjadi tidak efektif. Tujuan: Menganalisis hubungan viskositas saliva dengan kejadian karies gigi pada ibu hamil. Metode: Penelitian ini menggunakan metode literature review dengan prosedur naratif review. Penelusuran literatur dilakukan menggunakan Google Scholar dan PubMed. Hasil: Terdapat 30 jurnal yang memenuhi penelitian ini dengan jurnal tahun 2013-2020, jurnal berbahasa Indonesia dan Inggris, tersedia dalam bentuk full-text, jurnal dengan pembahasan viskositas saliva pada ibu hamil dan karies gigi pada ibu hamil. Kesimpulan: Terdapat hubungan viskositas saliva dengan karies gigi pada ibu hamil. Kata kunci: Ibu hamil, karies gigi, viskositas saliva